1989
DOI: 10.1248/cpb.37.1256
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiallergic activity of N-(4-(4-diphenylmethyl-1-piperazinyl)butyl)-1,4-dihydro-4-oxopyridine-3-carboxamides.

Abstract: A new series of oxopyridinecarboxamide derivatives 3a--g and 5a were synthesized and evaluated for their antiallergic activity. 1,4-Dihydro-7-methyl-4-oxo-1,8-naphthyridine-3-carboxamides 3a and 5a exhibited potent antiallergic activity (inhibitory rates of 80.7 and 88.3%, respectively, at 20 mg/kg, p.o.) in the rat passive cutaneous anaphylaxis (PCA) test and also exhibited much more potent in vitro inhibitory activity than caffeic acid against the enzyme 5-lipoxygenase (5-LO). Their in vitro antihistamine ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Nishikawa et al [51] synthesize oxo-pyridine carboxamide derivatives and evaluate their antiallergic activities. The 1, 8naphthyridine-3-carboxamides (43a and 43b) is found potent antiallergic agent in the rat passive cutaneous anaphylaxis (PCA) test and also exhibit excellent inhibitory activity in vitro than that of caffeic acid against 5-Lipoxygenase.…”
Section: Antihistaminic Activitymentioning
confidence: 99%
“…Nishikawa et al [51] synthesize oxo-pyridine carboxamide derivatives and evaluate their antiallergic activities. The 1, 8naphthyridine-3-carboxamides (43a and 43b) is found potent antiallergic agent in the rat passive cutaneous anaphylaxis (PCA) test and also exhibit excellent inhibitory activity in vitro than that of caffeic acid against 5-Lipoxygenase.…”
Section: Antihistaminic Activitymentioning
confidence: 99%
“…The recent wide applications of 2-propenoylamides, esters and 2-propenoyl chlorides in the synthesis of biologically and pharmacologically active compounds [330][331][332][333][334][335][336][337][338][339][340] and beside their uses in the synthesis of industriasl products make them worthy to be synthesized to obtain new structures of anticipated enhanced potency. Madkour et al reported the reaction and uses of 3-(4'-methoxyphenyl) and 3-(2'-thienyl)-2-cyano-2-propenoyl chloride in heterocyclic synthesis, as described in Scheme 157.…”
Section: Synthesis Of Other Heterocyclic Compoundsmentioning
confidence: 99%
“…In a preliminary pharmacological study, seven target benzenesulfonamides (4,7,8,12,19,20,28) and the intermediate v-hydroxy derivative 9 were tested (Table I). Although the number of studied compounds is limited it is obvious that (i) replacement of the butyl chain by a propyl one induces a clear decrease of activity in 4, (ii) the same dramatic effect was observed by introduction of a supplementary v-aminoalkyl fragment as observed with 7 and 8, (iii) replacement of the v-amino group by a piperidinyl one was also unsatisfactory, (iv) only introduction of an arylpiperazinyl -present in the SB reference compounds-or an amidino moiety succeeded in maintaining a level of activity comparable with that of JR435 (compounds 19, 20 and 28), (v) lastly, the presence of an v-cationic group seems to be critical for emergence of activity since SCHEME 4 Synthesis of arylpiperazine derivatives 19 and 20. the v-hydroxy compound 9 possesses no affinity for the studied model.…”
Section: Pharmacologymentioning
confidence: 99%